Clinical outcomes in patients with FLT3-ITD-mutated relapsed/refractory acute myelogenous leukemia undergoing hematopoietic stem cell transplantation after quizartinib or salvage chemotherapy in the QuANTUM-R trial - Ganguly, Siddhartha; Cortes, Jorge E.; Krämer, Alwin; Levis, Mark J.; Martinelli, Giovanni; Perl, Alexander E.; Russell, Nigel H.; Arunachalam, Meena; Santos, Cedric Dos; Gammon, Guy; Lesegretain, Arnaud; Mires, Derek E.; et al. (Transplantation and cellular therapy, 2021)
Despite the substantial clinical activity of fms-related tyrosine kinase 3 (FLT3) inhibitors in relapsed or refractory (R/R) FLT3-ITD‒positive acute myelogenous leukemia (AML), durable remissions and prolonged survival in this population require allogeneic hematopoietic stem cell transplantation (allo-HSCT). Quizartinib, a once-daily oral, highly potent, and selective FLT3 inhibitor, significantly prolonged overall survival (OS) and improved clinical benefit compared with salvage chemotherapy (median OS, 6.2 months versus 4.7 months; hazard ratio [HR], .76; 95% confidence interval [CI], .58 to .98; P = .018; composite complete remission [CRc] rate, 48% versus 27%; median duration of CRc, 2.8 months versus 1.2 months; mortality rate, .8% versus 14% by day 30, 7% versus 24% by day 60) in patients with R/R FLT3-ITD AML in the phase 3 QuANTUM-R trial. In this post hoc analysis, we described the characteristics of and clinical outcomes in patients who underwent on-study HSCT in QuANTUM-R at the investigator's discretion and institutional practices. Of 367 randomized patients, 78 (32%) in the quizartinib arm and 14 (11%) in the salvage chemotherapy arm underwent on-study allo-HSCT without any intervening therapy for AML after quizartinib or study-specified salvage chemotherapy. Pooled data of patients from both treatment arms showed a longer median overall survival (OS) in transplant recipients versus those treated without allo-HSCT (12.2 months versus 4.4 months; HR, .315; 95% CI, .233 to .427). Pooled data also showed a longer median OS in patients with a last recorded response of CRc before allo-HSCT versus patients without a CRc (20.1 months versus 8.8 months; HR, .506; 95% CI, .296 to .864). By treatment arm, the median OS was 25.1 months with quizartinib and 20.1 months with salvage chemotherapy in patients with a last recorded response of CRc before allo-HSCT. Forty-eight patients in the quizartinib arm continued quizartinib treatment after allo-HSCT. In the 31 patients with a last recorded response of CRc before allo-HSCT who continued quizartinib after allo-HSCT, the median OS was 27.1 months. Continuation of quizartinib after allo-HSCT was tolerable, and no new safety signals were identified. These results suggest that post-transplantation survival following salvage chemotherapy and quizartinib treatment are similar. However, quizartinib response occurs more frequently than with salvage chemotherapy, potentially allowing more patients to undergo transplantation and achieve durable clinical benefit. In addition, post-transplant quizartinib was found to be tolerable and may be associated with prolonged survival in some patients, highlighting its potential value in the management of patients with FLT3-ITD R/R AML.